Bentuk Penyajian Kesenian Kasidah Rebana Dalam Acara Pesta Perkawinan Di Jorong Saroha Tamiang Pasaman Barat - Marlisna Marlisna; Marzam Marzam (SENDRATASIK UNP, 2020)
This research aims to describe the form of a Kasidah Rebana presentation in a wedding party in Jorong SarohaTamiang, Lembah Melintang District, West Pasaman Regency. This research is a qualitative research which focuseson getting issues related to the topic. The data were collected through literature study, observation, interviews, and documentation. The development of sophisticated era and the cultures and arts developed in community give positive and negative effects. However, the art of Kasidah Rebana in the Jorong Saroha Tamiang still exists and is the choice of the community to be presented in a wedding party. The presentation form of Kasidah Rebana in the wedding party now has undergone many changes towards a more modern direction in accordance with the times. This can be seen from the sound system and formations, which neatly arranged by the group on stage, provided by the committee. Based on the composition, the rhythm pattern played is in accordance to the rhythmic musical instrument as well as the keyboard melody combined with chord harmonization and sound distribution. The vocalist sings the song according to the structure of the song's form and the expression according to the song's verse. These are combined to produce a beautiful tambourine blend. Based on the results of the study, to be more creative is an advice the author gives to the group. Song references, music compositions and costumes can be differently arranged, for instance. Thus, it is more interesting and more demanded by the community. The form of a Kasidah Rebana presentation is a mixed ensemble played by 12 players consisting of two vocalists, two tambourine players, two rhythm players, two bass players, three ketipung players, and one keyboard player.